Longitudinal investigation of the impact of anxiety and mood disorders in adolescence on subsequent substance use disorder onset and vice versa - Wolitzky-Taylor, Kate (2012)
OBJECTIVE: A large body of epidemiological research indicates that anxiety and mood disorders are highly comorbid with substance use disorders (SUDs). However, longitudinal research regarding their temporal relations is limited. The goal of this study was to assess whether emotional disorders (i.e., anxiety and mood disorders) predict the onset of SUDs, whether SUDs predict the onset of emotional disorders, or both. METHOD: The current study used data from baseline assessment (N = 627) and four years of follow-up assessments from the NU/UCLA Youth Emotion Project to examine this question. RESULTS: In line with the self-medication hypothesis of emotional disorder/SUDs comorbidity, anxiety and unipolar mood disorders at baseline assessment were associated with later onsets of SUDs. In particular, social anxiety disorder (SAD) at baseline predicted onset of alcohol use disorders and PTSD predicted the onset of all SUDs. SUDs did not predict any anxiety or unipolar mood disorders with the exception that alcohol use disorders predicted the onset of obsessive compulsive disorder (OCD). CONCLUSIONS: These findings, as well as the clinical implications and future directions for research, are discussed.